1995
DOI: 10.1161/01.cir.91.8.2264
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of In Vivo Tissue Temperature Profile and Lesion Geometry for Radiofrequency Ablation With a Saline-Irrigated Electrode Versus Temperature Control in a Canine Thigh Muscle Preparation

Abstract: Saline irrigation maintains a low electrode-tissue interface temperature during radiofrequency application at high power, which prevents an impedance rise and produces deeper and larger lesions. A higher temperature in the tissue (3.5 mm deep) than at the electrode-tissue interface indicates that direct resistive heating occurred deeper

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
413
6
6

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 573 publications
(443 citation statements)
references
References 29 publications
14
413
6
6
Order By: Relevance
“…Cooled RF ablation was more effective in terminating VT in the short-term, which is consistent with the production of a larger lesion, as seen in prior studies in animal models, in vitro preparations, and anecdotal observations. [7][8][9][10][11] Ablation was most effective at sites identified as likely isthmuses on the basis of entrainment and the presence of an isolated potential, as was previously reported. 5 In the present study, the termination rate at isthmus sites was significantly higher in the cooled RF group, suggesting that these reentry circuit isthmuses often exceed the width and depth of a standard RF lesion.…”
Section: Discussionsupporting
confidence: 73%
“…Cooled RF ablation was more effective in terminating VT in the short-term, which is consistent with the production of a larger lesion, as seen in prior studies in animal models, in vitro preparations, and anecdotal observations. [7][8][9][10][11] Ablation was most effective at sites identified as likely isthmuses on the basis of entrainment and the presence of an isolated potential, as was previously reported. 5 In the present study, the termination rate at isthmus sites was significantly higher in the cooled RF group, suggesting that these reentry circuit isthmuses often exceed the width and depth of a standard RF lesion.…”
Section: Discussionsupporting
confidence: 73%
“…RF energy was delivered according to a safe protocol found in experimental studies. 8,9 This consisted of temperature-controlled RF delivery with a power limit of 50 W, a target temperature of 45°C, and an infusion rate of 30 mL/min during RF delivery. Procedural success was defined as (1) termination and noninducibility of LAMRT and (2) conduction block across the tachycardia isthmus.…”
Section: Rf Ablationmentioning
confidence: 99%
“…Animal studies and clinical experience with epicardial ablation in the coronary veins using saline-irrigated electrodes have the potential for damage to the adjacent coronary artery. 30,31) Recently, Shimoike, et al reported two cases of successful ablation of LV outflow VTs from an endocardial site. 32) However, this site (left fibrous trigone) plays an important role in bridging aortic and mitral valve annuli.…”
Section: Discussionmentioning
confidence: 99%